Marketing Mix Analysis in the Implementation, Management of Transportation Services in the Era of Sustainable Globalization by Okky trans - Nofika Rahmayani; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2025)
Research purposes : The purpose of this analysis is to evaluate the influence of marketing mix strategies on service quality and customer satisfaction, identify effective strategies in improving operational efficiency and overcoming various challenges, and develop recommendations for optimizing marketing mix strategies to increase competitiveness. Design/Method/Approach: using descriptive qualitative research methods, data was collected through interviews, observations, and research-related documentation. Research Findings: This study found that the implementation of the marketing mix (7P) at Okky Trans successfully increased the company's competitiveness in the era of globalization. Strategies such as the use of digitalization for the ordering process, price transparency, social media-based promotions, and human resource training have a positive impact on customer satisfaction and loyalty. Theoretical contribution/Originality: This study makes a new contribution by integrating the 7P elements in the context of local transportation services in the era of globalization, highlighting the importance of digitalization and innovation in companies' marketing strategies. Practitioner/Policy Implications: The results of this study can help local transportation companies develop digital-based marketing policies and improve service quality to face global competition. Research limitations: This study is limited to the analysis of marketing mix strategies implemented by Okky Trans and only covers the tourism transportation service industry in Indonesia. External factors such as political and economic changes are not included in the scope of the study. Keywords : Marketing Mix, Transportation Services, Digitalization, 7P, Customer Loyalty, Globalization, Okky Trans